Emigree organisation lithuanian liberating activity. Publication of documents. - Rupšienė, Alisa (Genocidas ir rezistencija, 1999)
The publication seeks to shed light on liberation actions undertaken by diaspora organisations through sources. The documents are truly valuable and authentic; most of them have never been published before. They reflect the activities of various organisations, the difficulties they encountered in fulfilling their intentions and the obstacles that hindered their mutual cooperation. They are mainly correspondence between individual members of one organisation, or even between different organisations and official Lithuanian institutions in the USA.